Effect of Antiseptic Mouthwash as Water Substitute on Setting Time and Detail Reproduction of Alginate Impression Material - Putu Natasha Diska Agusjaya; Yosi Kusuma Eriwati; Sunarso (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Heating composite resins can reduce viscosity properties, increase adaptation to cavity walls, and facilitate application. There is still a lot of debate about the degree of microleakage and bond strength in preheated composites to determine how strong these composites are as cementation materials. Purpose: To analyze the strength level of preheated composite as cementation material in indirect adhesive restoration in terms of microleakage rate and bond strength. Methods: Preheating composite can reduce the viscosity of the composite to facilitate the placement of the composite and obtain better adaptation to the cavity wall. By analyzing the relevant references, the strength of the preheated composite material will be investigated by looking at the level of microleakage and the level of bonding between surfaces. Conclusion: Heating the composite to an appropriate temperature (50°C) can reduce microleakage and increase the micro-shear bond strength in the exposed dentin.